Norepinephrine titration in patients with sepsis-induced encephalopathy: cerebral pulsatility index compared to mean arterial pressure guided protocol: randomized controlled trial - Mai Salah Salem; Motaz Amr Abosabaa; Mohamed Samir Abd El Ghafar; Hala Mohey EI-Deen Mohamed EI-Gendy; Salah El-din Ibrahim Alsherif (BMC Anesthesiology)
Abstract Background Although surviving sepsis campaign (SSC) guidelines are the standard for sepsis and septic shock management, outcomes are still unfavourable. Given that perfusion pressure in sepsis is heterogeneous among patients and within the same patient; we evaluated the impact of individualized hemodynamic management via the transcranial Doppler (TCD) pulsatility index (PI) on mortality and outcomes among sepsis-induced encephalopathy (SIE) patients. Methods In this prospective, single-center randomized controlled study, 112 patients with SIE were randomly assigned. Mean arterial pressure (MAP) and norepinephrine (NE) titration were guided via the TCD pulsatility index to achieve a pulsatility index < 1.3 in Group I, whereas the SSC guidelines were used in Group II to achieve a MAP ≥ 65 mmHg. The primary outcome was intensive care unit (ICU) mortality and the secondary outcomes were; MAP that was measured invasively and values were recorded; daily in the morning, at the end of NE infusion and the end of ICU stay, duration of ICU stay, cerebral perfusion pressure (CPP), sequential organ failure assessment (SOFA) score, norepinephrine titration and Glasgow coma scale (GCS) score at discharge. Results ICU mortality percentage wasn`t significantly different between the two groups (p value 0.174). There was a significant increase in the MAP at the end of norepinephrine infusion (mean value of 69.54 ± 10.42 and p value 0.002) and in the GCS score at ICU discharge (Median value of 15 and p value 0.014) in the TCD group, and episodes of cerebral hypoperfusion with CPP < 60 mmHg, were significantly lower in the TCD group (median value of 2 and p value 0.018). Heart rate values, number of episodes of tachycardia or bradycardia, Total norepinephrine dosing, duration of norepinephrine infusion, SOFA score, serum lactate levels, and ICU stay duration weren`t significantly different between the two groups. Conclusions Individualizing hemodynamic management via the TCD pulsatility index in SIE patients was not associated with significant mortality reduction. However, it reduces episodes of cerebral hypoperfusion and improves GCS outcome but doesn’t significantly affect heart rate values, SOFA score, serum lactate level, length of ICU stay, total NE dosing, and duration of NE infusion. Trial registration The clinical trial was registered on clinucaltrials.gov under the identifier NCT05842616 https://clinicaltrials.gov/study/NCT05842616?cond=NCT05842616&rank=1 on 6-May-2023 before the enrolment of the first patient.